NILAI RELIGI PADA NOVEL 99 CAHAYA DI LANGIT EROPA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Izzati, Nurul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The aim of this research is to describe the values of religious in Novel â€œ99 Cahaya di Langit Eropaâ€ by Hanum Salsabiela Rais dan Rangga Almahendra of relationship human by Allah, human by human, human by world space. The method of this research by using the descriptive qualitative method.The researcher used structuralism approach. Structuralism method can be defined as see the values a novel by structure.After conducting this researcher it can be conclude that, 1) the religion values by realitionship of human by Allah is pray and dzikir can make heart calm. 2) the religion values by relationship human by human is help an dialog will make something better and make relationship stronger. 3) the religion values by relationship human by world space is greatfull of Allah creature, will make heart close to him because people know how powerfull his power in this world. The researcher hopes that this research can be the literature to help the teacher in teaching and learning process, and can be as the references for the other researcher who wants to conduct the research by using structuralism method. Â Keyword: religious values, structuralism analysis and novel